Música para ninar gente grande: a crítica social presente em produtos audiovisuais do rap brasileiro e no samba - Salines, Isadora Trois (Universidade do Vale do Rio dos Sinos, 2020)
Music is a powerful expression tool that entertains, educates, and creates awareness on their listeners. From video clips analysis, this research seeks to understand how visual and non-visual language are used to express social criticism. Samba and brazilian rap, the main objects of this research, are big examples of this phenomenon that music is. Based on the analysis of four video clips by four brazilian artists, this research permeates between the contexts of the two musical genres, and the scenarios in which they are inserted, seeking to identify concepts, characteristics and explanations that help to meet the central objective of the research: understand how visual and non-visual language are used to express social criticism.
Keywords: Comunicação; Música; Gênero Musical; Crítica social; Linguagem audiovisual; Communication; Music; Musical genre; Social criticism; Audio visual language